Pengaruh Strategi Active Learning Tipe Turnamen Terhadap Hasil Belajar Penyajian Data Di Kelas V Sekolah Dasar - Elsa Tinova; Risda Amini (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
This study aims to determine the effect of tournament type active learning strategies on the learning outcomes of data presentation in class V of Elementary School. This type of research is Quasi Experimental Design. The population in this study were fifth grade students of SD Gugus IV Padang Timur Kota Padang who had used the 2013 curriculum. The simple random sampling technique was obtained by SDN 11 Air Camar as the experimental group and SDN 10 Aur Duri as the control group. Based on the results of data analysis using t-test, obtained tcount = 2.501 and ttable = 2.026 at a significant level of 0.05 and dk = 37. It means that tcount > ttable, so H1 is accepted. Thus, there is a significant effect of tournament type active learning strategy on the learning outcomes of data presentation in class V of Elementary School.